Directed search for diuretics among 6-substituted pteridine-2,4,7(1H,3H,8H)-triones - K.V. Sokolova; V.V. Stavytskyi; S.I. Kovalenko; O.A. Podpletnya (Medičnì Perspektivi, 2022)
Directed search for biologically active compounds among heterocycles still remains a relevant area of medical chemistry. Among the significant number of heterocyclic compounds, pteridines deserve special attention. Among the above-mentioned ones the drugs with antitumor, antimicrobial, antiviral, diuretic and other types of biological action are known. Nevertheless, 6-substituted pteridine-2,4,7(1H,3H,8H)-triones, which are structurally similar to triamterene (6-phenylpteridine-2,4,7-triamine) – a diuretic with potassium-sparing action are interesting objects for search for diuretics. All the more, they are characterized by prototropic tautomerism, able to form hydrogen and donor-acceptor bonds with various ligands, and it is likely that these structural features will provide their diuretic effect. The aim of the study is the directed search for diuretics among 6-substituted pteridine-2,4,7(1H,3H,8H)-triones using in silico and in vivo methodology and elucidation of the probable mechanism of action. 1-methyl-3-R-6- (2-oxo-2-aryl- (hetaryl-) ethyl) pteridine-2,4,7(1H,3H,8H)-triones were selected to study the effect on renal excretory function. and 1-methyl-3-R-6- (2-hydroxy-2-aryl- (hetaryl-) ethyl) pteridine-2,4,7(1H,3H,8H)-triones. Directed search for compounds that affect the excretory function of the kidneys of rats was conducted by the conventional method of E.B. Berkhin with water load. The content of creatinine, sodium, potassium and chlorides in blood and urine plasma was determined by biochemical methods using standard test kits of NPV "Philisit-Diagnostics" (Ukraine) and calculations were performed according to generally accepted methods. Research of the probable mechanism was conducted by flexible molecular docking, as an approach of finding molecules with affinity to a specific biological target. Macromolecular data were downloaded from the Protein Data Bank (PDB) namely, the crystal structures of Human carbonic anhydrase II (PDB ID – 3HS4) and epithelial sodium channel (ENaC) (PDB ID – 4NTX). Studies of the effect of the synthesized compounds on the excretory function of the kidneys of rats showed that 1-methyl-3-R-6- (2-oxo-2-aryl- (hetaryl-) ethyl) pteridine-2,4,7(1H,3H,8H)-triones containing 4-fluorophenyl, 2,4-difluorophenyl, 4-chlorophenyl fragments in the molecule increase diuresis by the second hour by 27.3-70.1% compared with the control group. According to the results of the impact on daily diuresis, it was found that the most active was 1-methyl-6- (2-oxo-2-phenyl) ethyl) pteridine-2,4,7(1H,3H,8H)-triones, which increased daily diuresis by 168.1%, exceeding the effect of Hydrochlorothiazide (41.8%) and Triamterene (49.1%). However, substituted 1-methyl-3-R-6- (2-hydroxy-2-aryl- (hetaryl-) ethyl) pteridine-2,4,7(1H,3H,8H)-triones are inactive compounds. In-depth studies using biological tests and molecular docking have suggested that 1-methyl-6- (2-oxo-2-aryl) ethyl) pteridine-2,4,7(1H,3H,8H)-triones 2.1, 2.5 and 2.6) probable mechanisms of diuretic action are disruption of sodium transport in the distal convoluted tubules, causing sodium excretion and water loss and possibly inhibition of epithelial sodium channels that promote sodium uptake and potassium secretion in the distal convolutions and tubules, which implements potassium-sparing action. A well-founded and developed strategy for the search for diuretics among 6-substituted pteridine-2,4,7(1H,3H,8H)-triones has identified a number of effective compounds that by diuretic effect are superior to the reference drugs "Hydrochlorothiazide" and "Triamterene". Importantly, the results of molecular docking suggested a mechanism of action of the compounds under study, similar to thiazide diuretics. This action may be related to the tautomerism of these compounds and, as a consequence, their ability to form coordination bonds with the zinc cation and the additional interaction of halogens in the active site of CA II. It was possible to detect the presence of potassium-sparing action, probably due to the ability to inhibit epithelial sodium channels (ENaC). The obtained results substantiate the further purposeful search for potential diuretics among this class of compounds.